EVALUATION OF ANTIPSORIATIC ACTIVITY OF AQUEOUS EXTRACT OF BRASSICA OLERACEA VAR. CAPITATA AND ETHANOLIC EXTRACT OF MENTHA SPICATA LEAVES ON IMIQUIMOD-INDUCED PSORIASIS-LIKE DERMATITIS - HUSNA S, AYESHA; V, JAYASANKAR REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study is to evaluate the antipsoriatic activity of aqueous extract of Brassica oleracea var. capitata leaves (BOAE) and ethanolic extract of Mentha spicata leaves (MSEE) on Imiquimod-induced Psoriasis-like dermatitis. Methods: Imiquimod induction method for psoriasis-like dermatitis was used for the evaluation of antipsoriatic activity. Extracts were tested at a dose of 100 mg/kg body weight (b.wt.) and 400 mg/kg b.wt. in Swiss albino mice. These test doses were compared with the Retino-A (0.025%) treated group which serves as a standard group. Parameters studied in the test include changes in body weight, spleen weight and spleen index, neutrophils, lymphocytes, eosinophils, monocytes, hemoglobin, red blood cells, platelets, packed cell volume, mean corpuscular volume, mean corpuscular hemoglobin (MCH), MCH concentration, epidermal thickness, erythema, desquamation, skin thickness, superoxide dismutase, catalase, lipid peroxidation of skin and percentage orthokeratotic values, drug activity, and relative epidermal thickness. Results: MSEE at dose of 400 mg/kg b.wt has shown more effect when compared with MSEE at low dose, BOAE topical and oral. Conclusion: From the study, it was concluded that the above extracts have promising anti-psoriatic activity.